Optical microlever assisted DNA stretching - Andrew P-K; Raudsepp A; Fan D; Staufer U; Williams MAK; Avci E (Optica Publishing Group, 2021)
Optical microrobotics is an emerging field that has the potential to improve upon current optical tweezer studies through avenues such as limiting the exposure of biological molecules of interest to laser radiation and overcoming the current limitations of low forces and unwanted interactions between nearby optical traps. However, optical microrobotics has been historically limited to rigid, single-body end-effectors rather than even simple machines, limiting the tasks that can be performed. Additionally, while multi-body machines such as microlevers exist in the literature, they have not yet been successfully demonstrated as tools for biological studies, such as molecule stretching. In this work we have taken a step towards moving the field forward by developing two types of microlever, produced using two-photon absorption polymerisation, to perform the first lever-assisted stretches of double-stranded DNA. The aim of the work is to provide a proof of concept for using optical micromachines for single molecule studies. Both styles of microlevers were successfully used to stretch single duplexes of DNA, and the results were analysed with the worm-like chain model to show that they were in good agreement.
Keywords: DNA; Nucleic Acid Conformation; Optical Tweezers; Optics and Photonics; Proof of Concept Study; Robotics